Coulomb effects on thermally induced shuttling of spin-polarized electrons - Ilinskaya, O. A.; Shkop, A. D.; Radic, D.; Park, H. C.; Krive, I. V.; Shekhter, R. I.; Jonson, M. (Low temperature physics (Woodbury, N.Y.), 2019)
A thermally driven single-electron transistor with magnetic leads and a movable central island (a quantum dot) subject to an external magnetic field is considered. The possibility of a mechanical instability caused by magnetic exchange interactions between spin-polarized electrons in this system was studied by the density matrix method. We proved analytically that for noninteracting electrons in the dot there is no such mechanical instability. However, for finite strengths of the Coulomb correlations in the dot we numerically found critical magnetic fields separating regimes of mechanical instability and electron shuttling on the one hand and damped mechanical oscillations on the other. It was shown that thermally induced magnetic shuttling of spin-polarized electrons is a threshold phenomenon, and the dependence of the threshold bias temperature on model parameters was calculated.